Manajemen Sumber Daya Manusia Yang Unggul Dengan Kreativitas Dan Inovasi - Sugianto, Surya; Rokhaminawanti, Ersri; Purwanda, Eka (STIM-LPI Makassar, 2025)
The purpose of this research is to determine the extent to which creativity and innovation support the development of superior human resources. This study employs a qualitative approach with a literature review, focusing on theoretical insights to explore the relationship between creativity, innovation, and human resource development. The literature study method involves gathering and analyzing relevant sources, including books, journals, scientific articles, and official documents, without field data collection, to build a strong theoretical framework.The findings highlight the need for strategic approaches in achieving organizational goals, including organizational development, team collaboration, employee education, and training, all of which are critical for increasing productivity and work-life quality. Additionally, the importance of conducting Training Needs Assessments (TNA) as a foundational step in designing effective training programs is emphasized. The research explores three key management approaches: mechanistic, paternalistic, and social system, each addressing different strategies for managing human resources. Creativity and innovation are identified as vital components for achieving superior human resources. Creativity generates new ideas and products, while innovation enhances their value. Leadership plays a pivotal role in fostering an innovative organizational culture by providing autonomy, which promotes positive thinking, along with hard and soft skills. A structured organization with a strong ethical foundation and a supportive culture ensures the success of innovation.